Catalytic ethanolysis and gasification of kraft lignin into aromatic alcohols and H2-rich gas over Rh supported on La2O3/CeO2–ZrO2. (October 2016) - Yang, Jing; Zhao, Liang; Liu, Chunze; Wang, Yuanyuan; Dai, Liyi
Graphical abstract: Highlights: Efficient ethanolysis of kraft lignin was conducted over Rh/La2 O3 /CeO2 –ZrO2 . High yield aromatic alcohol was realized without aromatic rings hydrogenation. Excellent selectivity to H2 (82%) was observed in ethanol system. Possible reasons for deactivation of catalyst were analyzed. A relationship between deactivated catalyst and product distribution was proposed. Abstract: Efficient catalytic ethanolysis and gasification of kraft lignin were conducted over a versatile supported catalyst Rh/La2 O3 /CeO2 –ZrO2 to give high-value aromatic alcohols and H2 -rich gas. The removal of phenolic hydroxyl group was the most prevalent reaction, and importantly, almost no phenols, undesired char and saturating the aromatic ring were detected. Meanwhile, the feedstock and solvent both played key roles in H2 generation that contributed to the hydrodeoxygenation of liquid components and made the whole catalytic process out of H2 supply. Reusability tests of catalyst indicated that the crystalline phase transition and agglomeration of support, the loss of noble metal Rh and carbon deposition were the possible reasons for its deactivation in supercritical ethanol. Comparing with water, methanol and isopropanol system, ethanol was the only effective solvent for the depolymerization process.